STUDYING THE INFLUENCE OF FRACTIONAL COMPOSITION AND KINETICS OF MOISTURE SORPTION ON THE QUALITY OF CAPSULATED MASS AND CAPSULES“CELNINCIL” - Yunusova, Kh.M. (International Journal of Psychosocial Rehabilitation, 2020)
This report presents experimental data on the influence of technological factors and humidity on the quality indicators of “Tselnincil” capsules of the selected composition, which was determined using mathematical planning of the experiment using the 3 × 4 Latin square method. The effect of fractional composition, relative humidity, and moisture absorption kinetics on the quality indicators of Tselnincil capsules was studied. The obtained results are used to test capsule technology in a production environment. The method and mode of granulation are selected.